The Emerging Properties of Business Accelerators: The Case of Botswana, Namibia and Uganda Global Business Labs. Issue 1 (January 2017) - Ganamotse, Gaofetoge Ntshadi; Samuelsson, Mikael; Abankwah, Ruth, M.; Anthony, Tibaingana; Mphela, Thuso
Abstract: Entrepreneurship is an engine for economic development worldwide (Kelley, Singer, & Herrington 2016 ). For developing economies, the importance of entrepreneurship is associated with increased productivity and reduction in the rising unemployment rates, particularly among the youths. Consequently, several models and support programmes have been designed to facilitate successful entrepreneurial activities amongst youth. The article discusses the business acceleration model of the Global Business Labs (GBL) which is replicated in Botswana, Namibia and Uganda based on a Swedish model, between 2012 and 2015 but failed in Mozambique and Zambia. Using a multiple case study method, this article presents the results of a cross-country case analysis of the GBL programme with a view to understand the emergence of a business accelerator. Despite replication of the programme in respect of concepts, materials and operational systems, the cases reveal variations in operational experiences and acceleration performance across the five countries. Using the emergence theory, the article highlights these differences. The major contribution of the study to theory, in determining how business accelerators come into being, includes the duality of intentions and exchange between key stakeholders and the resource burst as a triggering mechanism in developing countries. The study further informs development of a model for successful business acceleration launch and subsequent performance for developing economies.